2018
DOI: 10.1186/s12872-018-0971-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of Klotho gene polymorphism with hypertension and coronary artery disease in an Iranian population

Abstract: BackgroundKlotho, possibly an age-regulating protein, is considered an important factor contributing to the lifespan and pathophysiology of hypertension and coronary artery disease (CAD). The present study was carried out aiming to investigate the association of Klotho-rs564481 (C1818T) gene polymorphism with hypertension and CAD.MethodsA total of 286 CAD-suspicious subjects were entered into this case-control study. The polymorphism was investigated in hypertensive patients with no CAD (H-Tens, n = 60); hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
(38 reference statements)
0
14
0
Order By: Relevance
“…A growing body of evidence has suggested that some single nucleotide polymorphisms in the klotho gene were correlated with the circulating klotho levels and the susceptibility to hypertension 24 , salt hypertension 8 , and coronary artery disease 25 as well as the onset of stroke 26 . Though we did not find a significant relationship between the serum klotho concentrations, blood pressure, and PWV, we cannot exclude the possibility that genetic polymorphisms of the klotho gene may be associated with blood pressure and arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence has suggested that some single nucleotide polymorphisms in the klotho gene were correlated with the circulating klotho levels and the susceptibility to hypertension 24 , salt hypertension 8 , and coronary artery disease 25 as well as the onset of stroke 26 . Though we did not find a significant relationship between the serum klotho concentrations, blood pressure, and PWV, we cannot exclude the possibility that genetic polymorphisms of the klotho gene may be associated with blood pressure and arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…KLB polymorphism is also reportedly related to coronary artery disease [20] and alcohol consumption [21]. In addition, studies in animals [11, 12] have shown that the AST/ALT ratio is elevated and triglyceride accumulation in the liver is increased in mice lacking KLB .…”
Section: Discussionmentioning
confidence: 99%
“…This observational study was performed on a total of 238 individuals who were admitted for coronary angiography to Shafa Hospital of Kerman University of Medical Sciences, Kerman, Iran (from July 2014 to December 2015). Subject selection process was conducted as described elsewhere [1719]. Briefly, all CAD-suspected participants were examined by coronary angiography, before which they went through CAD treatment as they were symptomatic, had a history of hospitalization in coronary care unit (CCU), or there was evidence of myocardial ischemia in noninvasive investigations such as an exercise test or perfusion imaging.…”
Section: Methodsmentioning
confidence: 99%